Rain Barrel Owners: Meeting the Programming Needs of the Unique Extension Audience - Emily Ott; Paul F. Monaghan; Wendy Wilber; Lynn Barber; Karissa Raymond (EDIS)
Rain barrels make it easy for households to practice water conservation. Extension programs for rain barrel construction, decoration, and giveaways can raise awareness for (and encourage use of) this technology. This 9-page document will provide insight into the behavior and attitudes of rain barrel owners so that Extension professionals may gain a better understanding of this unique audience. Written by Emily Ott, Paul Monaghan, Wendy Wilber, Lynn Barber, and Karissa Raymond and published by the UF/IFAS Department of Agricultural Education and Communication, March 2018. http://edis.ifas.ufl.edu/wc297